2013
DOI: 10.1186/1749-8090-8-67
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cyanosis following Kawashima operation: slow resolution after redirection of hepatic veins

Abstract: Progressive cyanosis often develops following Kawashima operation in patients with left atrial isomerism, interrupted inferior vena cava and hepatic veins draining to the atria. Knowledge on the timing and extend of resolution following hepatic venous redirection is sparse. A girl developed progressing cyanosis following Kawashima operation at the age of ten months. Arterial oxygen saturations at rest dropped to 60-65%. Surgical redirection of hepatic veins into the cavopulmonary circulation at the age of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, Larsen et al described that improvement in SpO 2 may take several months to occur, as they observed arterial oxygen saturations that improved over nine months to 90-93% and then eventually to 95-100% after three years. 3 Despite the late referral of our patient, recovery was noticed after completion of the HV inclusion as demonstrated by the increase in peripheral saturation up to 94% at one-year follow-up, regression of symptoms, and improvement in functional class.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Moreover, Larsen et al described that improvement in SpO 2 may take several months to occur, as they observed arterial oxygen saturations that improved over nine months to 90-93% and then eventually to 95-100% after three years. 3 Despite the late referral of our patient, recovery was noticed after completion of the HV inclusion as demonstrated by the increase in peripheral saturation up to 94% at one-year follow-up, regression of symptoms, and improvement in functional class.…”
Section: Discussionmentioning
confidence: 60%
“…Knowledge on the optimal timing and extent of resolution of PAVFs following hepatic venous redirection is sparse and controversial. 3 It has been reported that patients with the polysplenia form of heterotaxy syndrome (left isomerism) seem to be more prone to develop PAVFs after a Kawashima procedure, in which all systemic venous return except HV and coronary venous effluent is emptying to the pulmonary artery circulation, compared with patients with other forms of heart disease who undergo superior cavopulmonary connections. 1 Given the increasing evidence that the flow of HV blood to the lungs is critical to prevent PAVFs after superior cavopulmonary connection, one of the main priorities is constructing a pathway that minimizes the chances of significant streaming of HV flow toward one lung at the expense of the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the included studies were either case studies or case reports. [ 7 8 9 11 12 13 14 15 16 ] No manuscripts were excluded from this analysis due to concerns with study quality based on assessment using the National Heart, Lung, and Blood Institute Quality Assessment Tool for Case Series Studies. A total of 41 patients were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…1 Larsen et al reported an interval of nearly three years following HVI before saturations normalized 21 and also underscored the need for potentially earlier HVI that could accelerate resolution of cyanosis. Earlier HVI has similarly been suggested by Vollebregt et al 3 and others (McElhinney et al, 18 Larsen et al 21 ) to facilitate more expeditious resolution of PAVMs, though the optimal timing of HVI is not yet defined. The degree of hypoxia was only moderate in our cohort, reflecting our philosophy to offer HVI in the presence not only of profound desaturations but with exercise limitation or reduced functional status.…”
Section: Commentmentioning
confidence: 99%